Some epidemiological aspects of Myxosporean infections in Oreochromis niloticus (Linnaeus, 1758) and Hemichromis fasciatus (Peters, 1857), two cultured Cichlid fishes in the West - Cameroon - Fonkwa Georges; Nack Jacques; Kouam K Marc; Tomedi Eyango Minette; Tchoumboue Joseph (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2022)
In order to assess epidemiological aspects of myxosporean infection in cultured Oreochromis niloticus and Hemichromis fasciatus fishes in Cameroon to develop efficient prevention and control program, a total of 320 Cichlid fishes (189 Oreochromis niloticus and 131 Hemichromis fasciatus) were collected from June 2019 to April 2020 in the ponds located at the Ngoundoup Village, Koutaba Subdivision, Noun Division, Region of West-Cameroon. They were examined both macroscopically and microscopically for myxosporean infections. The prevalence of infection was determined as a function of fish species, sex, size, target organs, and seasons. Results showed that kidneys and ovaries were the only infected organs and harbored nine and three myxosporean species of the genus Myxobolus respectively. A total of 154 fish were infected (54.38%). Irrespective of the parasite species, Oreochromis niloticus (75.13%) was significantly more infected than Hemichromis fasciatus (24.27%). The prevalence of parasites was very low (<25%) whatever the fish species. The sex and fish size did not significantly influence the prevalence of parasite species. The prevalence of Myxobolus tilapiae was negatively and significantly correlated (r= -0.20; p= 0.02) with Oreochromis niloticus size. The overall prevalence was significantly higher during the dry season (88.76%) than during the rainy (75.31%) and the transitional (20.29%) seasons. Oreochromis niloticus was not infected during the transitional season while Hemichromis fasciatus was more infected (p<0.001) during the dry season (26.84%) followed by the rainy (15.80%) and the transitional (10.32%) seasons. The high prevalence of myxosporeans infection may decrease the fish farming yield. The epidemiological data recorded help develop prevention and control strategies to boost the production of Oreochromis niloticus and Hemichromis fasciatus in Cameroon.